Jesus and the Samaritan Woman: A Biblical Model for Youth Ministry - Yusuf, Obed L.; Chiroma, Nathan H. (2024)
Over the years, youth ministry has witnessed remarkable growth, transforming from a fledgling field into a fully-fledged Christian ministry and a viable profession. This growth gave its academicians the responsibility to conduct research and steer youth ministry in a biblical direction. In line with this great yet noble responsibility, this article explores Jesus’ conversation with the Samaritan woman in John 4 as a basis for developing a biblical model for youth ministry. The model in this article is constructed on a foundation that amalgamates insights gleaned from biblical narratives and developmental psychology. By exploring the story of Jesus and the Samaritan woman, as recorded in John 4:1–42, this article argued that the biblical model for youth ministry is to introduce young people to Jesus so they can believe in him as the Messiah and be incubated in his word to help them develop personal conviction, which will inevitably transform and lead them to exhibit love-rooted, grace-enabled actions.
Keywords: model John 4; Youth Ministry; youth workers; Samaritan Woman; Youth